Utilization of Organic Waste Into Compost Fertilizer: A Wise Solution to Manage Waste in Gebanganom Village, Kendal Regency - Ahmad Roudhi Multazami; Lutfiatun nur khasanah; Meita Nur Amalia; Monik Refiani; Dian Ika Aryani (Universitas Kristen Indonesia Toraja, 2024)
Activity Studying Work This is real (KKN) aiming For increase understanding and application use fertilizer compost in society Village Compost chosen as focus main Because its potential in support agriculture sustainable and reduce dependence to fertilizer chemistry . Through socialization This time , the KKN Posko 3 team invited Service Agriculture and Food Kendal Regency for can give education about benefit fertilizer compost , its production , and techniques its use in practice agriculture everyday. The method used For ensure effective knowledge transfer covering consultation , demonstration live , and discussion group . The results of activity This expected can increase awareness public will importance management rubbish organic and application fertilizer compost , so that in the end contribute to improvement productivity agriculture and sustainability environment in the village Gebanganom